Exploring the Interplay of Scale and Innovation: A Multidisciplinary Perspective (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
This paper explores the dynamic interplay between the concepts of scale and  in-novation, emphasizing the multifaceted and interdisciplinary nature of their  re-lationship. Drawing insights from human geography, political ecology, and  eco-nomics, the study delves into how scale—understood as hierarchical,  relational, and fluid—shapes and is shaped by innovative processes. It argues that  innovation is not only about the introduction of new products or processes  but also about their diffusion and adaptation across various scales. By  examining theories like “scale jumping” and “scale bending,” the paper  illustrates how organizations and innovators navigate different levels of  operation to optimize resources, align with socio-political contexts, and address  market demands. Through case studies the paper highlights the relational and  strategic dimensions of scale in innovation. It also addresses challenges such  as resource standardization, control dynamics, and localized policy needs.  Ultimately, the paper underscores the critical role of scale as a tool for fostering  sustainable and inclusive innovation, advocating for a nuanced understanding of  its implications in a globalized world.
Keywords: Scale; Innovation; Strategy; Policy; Management